Answer:
Last option:
![(x+1)^2+(y-1)^2=16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/btbbyrv4h73dzfslrteyyg1px62b2ulbq3.png)
Explanation:
The missing figure is attached.
The center-radius form of the circle equation is:
![(x - h)^2 + (y-k)^2 = r^2](https://img.qammunity.org/2020/formulas/mathematics/college/fe4jare77ui5712mncrefxfulq4mvcpgqj.png)
Where the center of the circle is at the poitn
and "r" is the radius.
You can identify from the figure attached that the radius of the circle shown is 4 units.
Since the other circle has the same radius and its center is at the point
; you can identify that:
![h=-1\\k=1\\r=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zhturfin00e2femn8rruuwfv3ithf3ko5k.png)
Therefore, substituting values into
, you get that the equation of that circle is:
![(x - (-1))^2 + (y-1)^2 = 4^2\\\\(x+1)^2+(y-1)^2=16](https://img.qammunity.org/2020/formulas/mathematics/middle-school/an8m8c2tn7alqvvoectyjh87ab604m79qj.png)